Extraction of biologically active substances from Siberian fir and effect of extracts on grain crops germination - Romanova, Margarita S.; Saveleva, Daria A.; Nuzhnykh, Svetlana A.; Zakharkiva, Alexandra M.; Mudrikova, Alena E.; Kazantseva, Ksenia I.; Poddubnyak, Alexander N.; Kurzina, Irina A. (Вестник Томского государственного университета. Химия)
This work considers methods of obtaining coniferous extracts containing triterpenic acids (TTAs) as the main active substance. Five coniferous extracts were obtained, the raw materials for their preparation were Siberian fir (Abies sibirica L.) wood greens, as well as extracted fir meal and oil-ester complex, both obtained after subcritical carbon dioxide extraction (CO2-extraction). In order to determine the composition of the obtained extracts, a method of analysis was developed and the study was conducted using high-performance liquid chromatography with mass spectrometric detection (HPLC-MS). The necessity of developing the new analytical method is the fact that the obtained extracts are samples with complex composition. It was found that the composition of the obtained samples includes triterpenic, fatty and resin acids. Seeds of grain crops - spring wheat and spring barley were taken as biological test objects. Laboratory study of the effect of the obtained coniferous extracts on germination, germination energy and morphometric parameters was conducted, for this purpose seeds were treated with aqueous solutions of the obtained coniferous extracts. Samples 1 and 5 showed the greatest stimulating effect, which is manifested, among other, in an increase in the length and mass of sprouts and an increase in mass of 1 plant. The effect of coniferous extracts on seed pathogens of spring wheat in standard phytopathological analysis was also evaluated. The decrease by 1.4 times relatively to the control of total infestation of wheat seeds with seed infection pathogens while using the sample 3 was observed. The obtained data show the perspective of further research in obtaining and studying samples based on Siberian fir extracts for use in agriculture as growth-stimulating and fungicidal preparations.